Global, regional, and national burden and trends analysis of gallbladder and biliary tract cancer from 1990 to 2019 and predictions to 2030: a systematic analysis for the Global Burden of Disease Study 2019 - Su, Jiao; Liang, Yuanhao; He, Xiaofeng (Frontiers in Medicine, 2024)
Objectives: Our aim was to explore the disease burden caused by gallbladder and biliary tract cancer globally, regionally, and nationally, by age and sex. Methods: The absolute number of cases and age-standardized rates (ASR) of incidence, prevalence, mortality, and disability-adjusted life years (DALYs) due to gallbladder and biliary tract cancer were extracted from the Global Burden of Disease (GBD) Study 2019. We estimated the trends in disease burden by calculating the percentage change in the absolute number of cases and the estimated annual percentage change (EAPC) in ASR, by social development index (SDI), region, nation, sex, and age. Results: From 1990 to 2019, the number of incident cases, prevalent cases, deaths, and DALYs worldwide significantly increased by 1.85-fold, 1.92-fold, 1.82-fold, and 1.68-fold, respectively. However, the age-standardized rates of incidence, prevalence, mortality, and DALYs tend to decrease globally over time. Nevertheless, heterogeneous disease burden patterns exist between geographic regions due to different geographical risk factors, distinct epidemiologically predominant gallbladder and biliary tract cancer subtypes, and potential genetic predispositions or ethnicity. Additionally, socioeconomic status mediates the regional variation in disease burden, with increasing SDI or HDI scores associated with downward trends in the age-standardized rates of incidence, prevalence, mortality, and DALYs. Older individuals and females are at higher risk of gallbladder and biliary tract cancer, but the increasing burden of early-onset gallbladder and biliary tract cancer is a cause for concern, especially for those living in lower SDI areas and males. High BMI is the primary risk factors underlying gallbladder and biliary tract cancer, accounted for 15.2% of deaths and 15.7% DALYs globally in 2019. Conclusions: Our study comprehensively elucidated the distribution and dynamic trends of gallbladder and biliary tract cancer burden over the past three decades, from multiple dimensions. These findings emphasize the importance of promoting a healthy lifestyle as a population-level cancer prevention strategy and tailoring cancer control actions based on localized risk factors and the epidemic profiles of gallbladder and biliary tract cancer by anatomical subtype.